Are pollinators the agents of selection for the extreme large size and dark color in Oncocyclus irises?. Issue 1 (26th August 2014) - Lavi, Renana; Sapir, Yuval
Summary: Pollinator‐mediated selection is a major evolutionary driver of floral traits; yet, such selection has rarely been tested for floral extreme traits. The Oncocyclus irises have exceptionally large, dark‐colored flowers, associated with night‐sheltering pollination and heat reward by the dark flowers. We quantified phenotypic selection on stem length, floral size and color in two species of iris ( Iris atropurpurea and I. haynei ), using an experimental approach. We estimated selection gradients for both flowers open to natural pollination and for flowers receiving supplementary hand pollination, assuming that open‐pollinated flowers are affected by all factors that could influence fitness, whereas supplementary pollination removes the possible influence of pollinators. We found evidence for pollinator‐mediated selection to increase floral size and stem length in I. atropurpurea, but floral color in this species was not under pollinator‐mediated selection. In I. haynei, no pollinator‐mediated selection on any of the traits was detected. We conclude that the extreme floral size of I. atropurpurea has probably evolved as a result of pollinator behavior. Lack of such evidence for I. haynei and for the dark floral color in both species suggests that other non‐pollinator agents are selecting for these prominent traits, or that phenotypic color variation in these irises is neutral.